Green Synthesis and Characterization of Gold Nanoparticles for Antibacterial and Antifungal Activities Using Leaf Extracts of Annona Muricata - Shahi, Dr. Sanyogita; Shilja (Migration Letters, 2023)
The necessity of disclosing the expeditious synthesis, non-hazardous nature, cost-effectiveness, and environmentally friendly approaches for synthesizing nanoparticles using plants is highly significant. The observed phenomenon can be attributed to the elevated toxicity levels inherent in the chemical approach employed for nanoparticle synthesis. The use of plants for synthesizing metal nanoparticles has garnered significant interest among researchers, owing to the distinctive characteristics of these nanoparticles and their wide-ranging applications across several sectors. This paper aimed to assess the efficacy of the synthesized Gold Nanoparticle (GNP) against certain human diseases. The synthesis of GNP has been accomplished by the reaction between a gold chloride solution and a leaf extract derived from Annona muricata. The GNP was characterized using a Transmission Electron Microscope (TEM) and Fourier Transformed Infrared spectroscopy (FTIR). The morphology, size, and structural characteristics of the GNP that have been synthesized are assessed using TEM analysis. The research revealed that the nanoparticles exhibited a spherical shape and were uniformly distributed, with a mean particle dimension of 26.5 nm. The FTIR analysis demonstrates that peaks within the mid-range wavenumbers, namely in the region of 1700-1300 1/cm, indicate the potential existence of organic molecules such as phenols, aliphatic amines, and carboxylic acids. These functional groups play a crucial role in the capping and stabilizing processes of the GNP that were produced. The synthesized GNP with sustainability were assessed for their antibacterial and antifungal properties. The results demonstrated a modest level of antibacterial activity and antifungal activity. The leaf extract of Annona muricata, rather than being discarded, may be effectively utilized to produce GNPs. These nanoparticles can serve as a natural source of antibacterial and antifungal agents.